(untitled) (Global Journal of Science Frontier Research, 2023)
It is of great practical significance to test and analyze the quality of silicon materials used in integrated devices and their changes in planar thermal process. This paper summarizes the international test, analysis and research results. The contents include polycrystal preparation, single crystal growth and its crystal defects, wafer cutting, grinding and polishing, wafer tracking observation and analysis in plane thermal process, generation control and elimination of induced dislocations, etc.